Research Trends of Nobel Laureate Brian P Schmidt: A Scientometric Study - Sedam, Mariraj Vasudev; Keshava (Information Research Communications, 2025)
Background The Nobel Prize in Physics has been awarded 114 times to 216 laureates between 1901 and 2020, with John Bardeen being the only double recipient. Brian P. Schmidt is one of the 215 individual laureates whose scientific output reflects significant contributions to astrophysics. Objectives To examine the publication productivity, authorship pattern, and communication channels of Physics Nobel Laureate Brian P. Schmidt through a scientometric approach. Materials and Methods Data on Schmidt’s research publications were collected and analysed to determine publication trends, collaborative authorship, and preferred journals. Results Findings indicate high research productivity, extensive multi-authored publications, and frequent dissemination through leading physics and astronomy journals. Conclusion Brian P. Schmidt’s scholarly output demonstrates strong productivity, high collaboration, and consistent use of prominent scientific communication channels.
Keywords: Authorship Credit; h-Index; Nobel Laureates; Publication Productivity; Scientometric Portrait; Scientometrics.